Integrating aquaculture with crop systems : an aquaponic enterprise project proposal for the Ntinga Multipurpose Co-Operative in Philippi, South Africa - Van der Merwe, Marnus (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.